Complementary bidding and the collusive arrangement: Evidence from an antitrust investigation - Robert Clark; Decio Coviello; Adriano de Leverano (Queen's University, Department of Economics, 2020)
A number of recent papers have proposed that a pattern of isolated winning bids may be associated with collusion. In contrast, others have suggested that bid clustering, especially of the two lowest bids, is indicative of collusion. In this paper, we present evidence from an actual procurement cartel uncovered during an anticollusion investigation that reconciles these two points of view and shows that both patterns arise naturally together as part of a cartel arrangement featuring complementary bidding. Using a difference-in-difference approach, we compare the extent of winning-bid isolation and clustering of bids in Montreal's asphalt industry before and after the investigation to patterns over the same time span in Quebec City, whose asphalt industry has not been the subject of collusion allegations. Our findings provide causal evidence that the collusive arrangement featured both clustering and isolation. We use information from testimony of alleged participants in the cartels to explain how these two seemingly contradictory patterns can be harmonized.
Keywords: L22; L74; D44; H57; 330; Auction; Bidding ring; Collusion; Complementary bidding; Clustered bids; Missing bids; Public procurement